The representation of the memory of the soldiers in Ese camino existe by Luis Fernando Cueto Chavarría - Málaga Diestro, Ángel José (2023)
This article proposes to describe and understand, in the light of the analysis of the novel Ese camino existe by Luis Fernando Cueto, the processes of memory formation and forgetfulness of the internal armed conflict (CAI) that occurred in Peru during the 1980s and 2000, through the different actors represented in the play, to then individualize the memory of one of the actors who had direct participation, but who, for different reasons, could not speak and his voice, and therefore his memory, have not been made visible: the soldiers. For this, we will rely on studies that reflect on the category of memory, based on the work of Elizabeth Jelin. The analysis of the representation of the memory of the soldiers will show that, in order to build a “restorative” memory, it is necessary that all the memories of the CAI actors be made visible.